2010
DOI: 10.1111/j.1365-2052.2010.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural annotation of equine protein‐coding genes determined by mRNA sequencing

Abstract: SummaryThe horse, like the majority of animal species, has a limited amount of species-specific expressed sequence data available in public databases. As a result, structural models for the majority of genes defined in the equine genome are predictions based on ab initio sequence analysis or the projection of gene structures from other mammalian species. The current study used Illumina-based sequencing of messenger RNA (RNA-seq) to help refine structural annotation of equine protein-coding genes and for a prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…With the difficulty in working with large animals, there is a lack of expressed sequence tag (EST) data, hence the current annotation of the protein coding regions of the horse genome is largely derived from extrapolation from the genes of other species (Coleman et al, 2010). This is beginning to be redressed with several recent papers outlining transcription profiles using digital gene analysis of a variety of horse tissues including muscle, leukocytes, cartilage, brain, reproductive tissue, embryos, sperm and blood (Capomaccio et al, 2013; Coleman et al, 2010; Das et al, 2013; Iqbal et al, 2014; McGivney et al, 2010; Park et al, 2012; Serteyn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the difficulty in working with large animals, there is a lack of expressed sequence tag (EST) data, hence the current annotation of the protein coding regions of the horse genome is largely derived from extrapolation from the genes of other species (Coleman et al, 2010). This is beginning to be redressed with several recent papers outlining transcription profiles using digital gene analysis of a variety of horse tissues including muscle, leukocytes, cartilage, brain, reproductive tissue, embryos, sperm and blood (Capomaccio et al, 2013; Coleman et al, 2010; Das et al, 2013; Iqbal et al, 2014; McGivney et al, 2010; Park et al, 2012; Serteyn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is beginning to be redressed with several recent papers outlining transcription profiles using digital gene analysis of a variety of horse tissues including muscle, leukocytes, cartilage, brain, reproductive tissue, embryos, sperm and blood (Capomaccio et al, 2013; Coleman et al, 2010; Das et al, 2013; Iqbal et al, 2014; McGivney et al, 2010; Park et al, 2012; Serteyn et al, 2010). Capomaccio et al (2013) identified new putative non-coding sequences within intergenic and intronic regions whilst Das et al (2013) suggested additions to the structural annotation of four sperm genes.…”
Section: Introductionmentioning
confidence: 99%
“…This modern method of analyzing global gene expression profiles was first used in horses in 2010 by Coleman et al With the use of the RNA-seq method, authors have analyzed th transcriptomes of several equine tissues (including cartilage, placenta, testis, cerebellum, embryonic tissue) and refined the structural annotation of more than 11,000 protein-coding genes annotated previously in the Ensembl database as predicted genes (Coleman et al 2010). Authors have also identified 456 new transcripts which were not listed in the Ensembl or NCBI databases.…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tmentioning
confidence: 99%
“…Authors have also identified 456 new transcripts which were not listed in the Ensembl or NCBI databases. Moreover, Coleman et al (2010) reported tissue-specific expression profiles of thousands of genes and this type of research allowed for comprehensive functional and structural analysis of numerous genes in the horse genome. Further studies based on the results obtained from sequencing of the whole transcriptome (RNA-seq) allowed to identify 428 putative transcripts that have not been annotated in the Ensembl database and showing no homology to known protein-coding genes described in other species (Coleman et al 2013).…”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tmentioning
confidence: 99%
“…To the authors' knowledge, the first report of RNA‐Seq in horses was an effort to characterize the transcriptome and tissue‐specific expression profiles from 8 equine tissues 94. A subsequent study focused on characterizing gene expression by RNA‐Seq in immunologically active tissues 95.…”
Section: Next Generation Sequencing Techniquesmentioning
confidence: 99%